Co-administration of Systemic and Intralesional Zoledronic Acid in a Case of Fibrous Dysplasia: A Potentially Novel Therapy - Bhadada, Sanjay Kumar; Pal, Rimesh; Sood, Ashwani; Dhiman, Vandana; Saini, Uttam Chand (Frontiers in Endocrinology, 2019)
Fibrous dysplasia (FD) is a benign bone lesion characterized by replacement of normal bone with abnormal fibrous tissue, clinically manifesting as deformities, bone pains and pathological fractures. The standard medical management for FD includes systemic bisphosphonate therapy. The efficacy of systemic bisphosphonate is however limited with minimal functional improvement and pain relief. Keeping the above lacunae in mind, we have made a solitary attempt at treating FD with locally administered zoledronic acid. A 25-year-old gentleman had presented to our institute with swelling and pain involving the left thigh and left lower leg. He was diagnosed as having polyostotic FD, confirmed on bone histopathology. He was administered 4 mg of zoledronic acid intravenously while 1 mg of the drug was injected locally into the femoral lesion under ultrasound and fluoroscopy guidance. There were no peri-procedural complications. At 6 months follow-up, there was marked improvement in pain scores at the left thigh, while that at the left leg remained unchanged. In addition, repeat bone scintigraphy showed a 20.8% and 25.3% reduction in anterior and posterior uptake values, respectively, at the left femur while that at the left tibia remained unchanged.